Longitudinal Observational Analysis of Traumatic Brain Injury Epidemiology and Pre-Hospital Intervals During the COVID-19 Pandemic in a West Java Tertiary Center - Ni Wayan Lisa Suasti; Akhmad Imron; Guata Naibaho (HM Publisher, 2026)
Background: The COVID-19 pandemic necessitated large-scale social restrictions (PSBB) in Indonesia, drastically altering population mobility and, consequently, the landscape of neurotrauma. While the reduction in road traffic Incidents (RTIs) during lockdowns is well-documented, the collateral impact on the golden hour—the critical pre-hospital interval for traumatic brain injury (TBI) resuscitation—remains under-researched in lower-middle income countries (LMICs). This study analyzes the longitudinal shifts in TBI epidemiology, injury mechanisms, and hospital admission intervals across pre-pandemic, pandemic, and relaxation phases. Methods: This retrospective observational study analyzed 1,519 TBI patients admitted to the Emergency Department of Dr. Hasan Sadikin General Hospital (RSHS), a tertiary referral center in West Java, from January 2019 to December 2021. The cohort was stratified into three phases: Pre-Pandemic (2019), Pandemic/PSBB (2020), and Relaxation (2021). Variables included demographics, injury mechanisms, Glasgow Coma Scale (GCS), loss of consciousness (LOC), and Hospital Admission Interval (MRS). Results: Total TBI admissions exhibited a sharp V-shaped trend, decreasing by 75% in 2020 compared to 2019, driven by a collapse in RTI volume (490 to 107 cases). Admissions rebounded in 2021 (n=705). Males (78.4%) and young adults (15-24 years) constituted the majority, with RTI accounting for 74.78% of all mechanisms. While pediatric (0-4 years) and geriatric (≥65 years) groups were prone to falls, the most critical finding concerned pre-hospital delays. Despite reduced traffic density, only 3.23% of patients arrived within the golden hour (<1 hour). The majority (40.42%) arrived between 5-12 hours, and a significant cohort (17.44%) experienced delays exceeding 12 hours, indicating persistent systemic barriers to rapid care regardless of road conditions. Conclusion: The pandemic successfully suppressed TBI volume through mobility restrictions but failed to improve pre-hospital admission times. The persistence of significant delays (>5 hours) for the vast majority of patients highlights that the barriers to the golden hour in Indonesia are structural rather than traffic-dependent. Future trauma systems must address these pre-hospital inefficiencies to improve outcomes.